x + 7 = 18;
х=18-7;
х=11.
ответ:11.
11 + x = 18;
х=18-11;
х=7.
ответ:7.
11 + 7 = x;
х=11+7;
х=18.
ответ:18.
x + 11 = 29;
х=29-11;
ответ:18
18 + x = 29;
x = 29 - 18;
x = 11.
18 + 11 = х;
х = 18 + 11;
х = 29.
ответ:29.
x - 2 = 9;
x = 9 - 2;
11 - x = 9;
x = 11 - 9;
x = 2.
ответ:2.
11 - 2 = x;
x = 11 - 2;
x = 9.
ответ:9.
Пошаговое объяснение:
(когда мы преобразуем примеры в уравнение можно использовать любые буквы латинского алфавита я буду использовать x)
x + 7 = 18;
х=18-7;
х=11.
ответ:11.
11 + x = 18;
х=18-11;
х=7.
ответ:7.
11 + 7 = x;
х=11+7;
х=18.
ответ:18.
x + 11 = 29;
х=29-11;
х=18.
ответ:18
18 + x = 29;
x = 29 - 18;
x = 11.
ответ:11.
18 + 11 = х;
х = 18 + 11;
х = 29.
ответ:29.
x - 2 = 9;
x = 9 - 2;
x = 11.
ответ:11.
11 - x = 9;
x = 11 - 9;
x = 2.
ответ:2.
11 - 2 = x;
x = 11 - 2;
x = 9.
ответ:9.
Пошаговое объяснение:
(когда мы преобразуем примеры в уравнение можно использовать любые буквы латинского алфавита я буду использовать x)